"You are so ugly, you whore"- girls in rural Sweden discuss and address gendered violence. Issue 1 (1st January 2020) - Brännström, Lotta; Nyhlén, Sara; Gillander Gådin, Katja
ABSTRACT: Girls face gendered violence on an everyday basis, and this may have severe health consequences. Purpose: The aim of this study was to learn about gendered violence facing girls in rural Sweden in their everyday life, as it is experienced by the girls themselves. Method: Using the photovoice method, we worked with 35 girls in an upper secondary school, aged between 16 and 20, to explore how they navigated social spaces and developed strategies for increased safety. Results: Thematic analysis revealed two main themes ( constant fear and strategies ) and four sub themes ( fear of being raped, fear of being labelled and excluded, being "appropriately" sexually active, and appearance and performance for increased feelings of safety ). Conclusion: We considered how gendered violence facing girls led to fear and marginalization in a range of situations and interactions. Consequently, girls occupied significantly smaller social spaces compared to boys, and we argue that this was reproduced and upheld through everyday practices informed by hegemonic masculinity and performativity.